Leadership, Gender, and Organization - Werhane, Patricia; Painter-Morland, Mollie; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2011)
This text provides perspectives on the way in which gender plays a role in leadership dynamics and ethics within organizations. We are also interested in understanding how women engage in other forms of social organization, i.e. organization that goes beyond, or operates outside of formal institutions or assigned positions of authority. This text seeks to explore new theoretical models for thinking about leadership and organizational influence. Most studies of women$1 (Bs leadership draw on an ethics of care as characteristic of the way women lead, but as such, it tends towards essentialist gender stereotypes and does little to explain the complex systemic variables that influence the functioning of women within organizations. This book moves beyond the canon in exploring alternative paradigms for thinking about leadership and gender in organizations, and about the role women play in organization, understood here also as a verb, not just a noun. The authors draw on the literature available in systems thinking, systemic leadership, and gender theory to offer alternative perspectives for thinking about the ways women lead.The book offers invaluable theoretical perspectives and insightful narratives to graduate students and researchers who are interested in women$1 (Bs leadership, gender and organization. It will be of interest to all women in leadership positions, but specifically to those interested in understanding the systemic nature of leadership.s
Introduction -- An Historical Perspective -- It is Not Your Mother$1 (Bs Feminist Movement; Mary Hartman -- Transformational Leadership and Systems Thinking -- Ways Women Lead; Judy B. Rosener -- Women Leaders in a Globalized World; Patricia H. Werhane -- Systemic Leadership: Ethical and Effective; Jane Collier and Rafael Esteban -- Relational Leadership, Gender, and Complexity Leadership Theory -- Relational Leadership and Gender: From Hierarchy to Relationality; Mary Uhl-Bien -- Relational Leadership Theory; Mary Uhl-Bien -- Complexity Leadership Theory: Shifting Leadership from the Industrial Age to the Knowledge Era; Mary Uhl-Bien, Russ Marion, and Bill McKelvey -- Systemic Leadership in Gendered Organizations -- Systemic leadership, Gender and Organization; Mollie Painter-Morland -- Leadership in Practice -- Negotiating Ambivalence: The Leadership of Professional Women$1 (Bs Networks; Ine Gremmen and Yvonne Benschop -- Why do They Leave? Voluntary Turnover of South African Women Executives; Desray Clark and Nicola Kleyn -- Empowering Women Empowering Cultures; Deirdre Tedmanson -- When Teens Organize: Lessons from Chicago's Community Accountability Movement; Kristin McCarthy -- Women Leading a Responsible Global Business: Dame Anita Roddick, Founder of the Body Shop; Nicola M. Pless -- Conclusion -- About the Authors.s
Keywords: Philosophy (General).; Ethics; Social legislation; Humanities; Economics; Developmental psychology; Philosophy; Ethics; Gender Studies; Business/Management Science, general; Interdisciplinary Studies; Labour Law/Social Law